Kajian Perilaku Kelompok dalam Organisasi - Abidin, Jainul; Suryani, Yani (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Humans are social creatures. Cannot stand alone without the help of others. Social beings in their lives need other people. In dealing with other people, humans eventually form a group. Groups that are formed or built are usually because there are similarities behind the group. From some opinions of experts, it can be concluded that a group is a collection of two or more people who interact with each other. In the interaction, there are goals to be achieved. The key word for a group is that there are two individuals who interact each other to achieve a common goal. The opinion of Henry Murray and David Mc Clelland and McAdam in Dayakisni (2006: 157) there are two social motives that encourage a person to have relationships with other people, namely; Need of Affiliation (the need for affiliation), namely the desire to establish and maintain several rewarding interpersonal relationships, and the need for intimacy, namely choosing a warm, close and communicative relationship. As it develops, the group becomes an organization. The organization is a group of people who are working towards a common goal under leadership (Davis: 1951). This means that this is one of the things that distinguishes organizations from groups. The method used in this research is literature study, namely by looking for various relevant sources to support the theory of this research. From various sources obtained, it can be concluded that the success or failure of the organization in achieving its goals depends on how far a leader is able to influence his subordinates so that they are able to work with high morale and organizational goals can be achieved efficiently and effectively.